A rare presentation of ovarian fibrothecoma: a diagnosing dilemma - Logesh, Kalaivani; Prasanna, Latha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Ovarian Fibrothecoma are uncommon tumors of gonadal stromal cell origin accounting for 3-4% of all ovarian tumours. Ovarian fibrothecoma are composed of an admixture of fibrous and the comatous elements. The stromal cell tumors are probably the most inaccurately diagnosed tumor of the female gonad, clinically and histologically. Rarely benign tumours can present with elevated CA125. Here we discuss a rare presentation of Ovarian Fibrothecoma in a 52 years postmenopausal woman with large pelvic mass with ascites and elevated CA125 which we mistook for malignancy. Hence accurate diagnosis is more important before extensive surgical intervention.